Water Purification Using SPZ and SPA Filter Media to Improve the Water Quality of Sekar Lepen Keprabon River - Herlina Noor Agustin; Sunarto Sunarto; Hashfi Hawali Abdul Matin (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
The Sekar Lepen Keprabon River is one of the tributaries polluted by domestic waste. This study aims to determine the water quality of the Sekar Lepen Keprabon River before and after filtering using SPZ (coconut fiber, banana fronds, zeolite stone) and SPA (coconut fiber, banana fronds, coconut shell charcoal) filter media. This experiment uses SPZ and SPA filter media to purify water that is applied directly to the river. The methods used were primary and secondary data collection. The data obtained were analyzed using a descriptive quantitative approach and the effectiveness of each parameter was calculated. The results of this study indicate that the water quality before and after filtering with SPZ filter media obtained a fixed temperature value, pH increased, COD and TSS increased, and TDS decreased. Water quality before and after going through the SPA filter media obtained a fixed value in temperature, pH increased, COD and TSS decreased, and TDS increased. SPZ filter media in the water filtration process is more effective in increasing pH parameters and reducing TDS parameters in river water. In contrast, SPA filter media in the water filtration process is more effective in reducing COD and TSS parameters in river water.